Impact of Irrigation Practices on Production and Water Productivity of Transplanted Rice Under NSP Canal Command Area - Rao, S. Srinivasa; Naik, B. Balaji; Ramulu, V.; Devi, M. Uma; Shivani, D. (International Journal of Bio-resource and Stress Management, 2020)
The two years adoptive research work carried out to study the effect of alternate wetting and drying method of irrigation and submerged irrigation method (Control) on water use, water productivity and yield of paddy during kharif season (June to November, 2014-15 and 2015-16) in farmer’s field under NSP canal command area of Khammam district, Telangana. Soil was clay loam, mild alkaline, low in available nitrogen, medium in available Phosphorus and Potassium. Field capacity and permanent wilting point of soil was 28.7, 14.9%, respectively. Results were shown as highest effective tillers and number of panicles per square meter inturn resulted as higher grain and straw yields in alternate wetting and drying method of irrigation over the submerged irrigation method. Over the years, lower water input (mm ha-1) at 795 mm to 1180 mm and higher water productivity at 0.52 to 0.66 kg m-3 resulted with alternate wetting and drying method of irrigation and it saved the water at 20.2 to 23.4% over control. Due to intermittent irrigation application to maintain the soil saturation at critical stages avoided moisture stress and resulted better crop growth and produced higher yields with lower water usage inturn saved the irrigation water and it would get the higher water productivity in alternate wetting and drying method irrigation. This may provide the valuable information on the aspect of alternate wetting and drying method of irrigation to get the higher yields and water productivity in paddy.